Health and school performance of teenagers born before 29 weeks gestation. Issue 3 (1st May 2003) - Johnson, A; Bowler, U; Yudkin, P; Hockley, C; Wariyar, U; Gardner, F; Mutch, L
Abstract : Objective: To ascertain the health and school performance of teenagers born before 29 weeks gestation (extremely low gestational age (ELGA)) and to compare those in mainstream school with classroom controls. Methods: Three geographically defined cohorts of babies born in 1983 and 1984 were traced at the age of 15–16 years. Their health, abilities, and educational performance were ascertained using postal questionnaires to the teenagers themselves, their parents, their general practitioners, and the teachers of those in mainstream school. Identical questionnaires were sent to classroom controls. Results: Of the 218 teenagers surviving to the age of 16 years, information was obtained on 179. Of these, 29 were in special schools and 150 in mainstream school, 10 of whom had severe motor or sensory impairment. Using the Child Health Questionnaire, parents of teenagers in mainstream school reported a higher incidence of problems than controls in physical functioning (difference in mean scores 9.0 (95% confidence interval (CI) 4.9 to 13.1)) and family life (difference in mean scores for family cohesion 7.0 (95% CI 1.6 to 12.4)). In all areas of learning, teachers rated the ability of the ELGA teenagers in mainstream school lower than the control group. Parents of teenagers in special schools reported a higher rate of problems in most areas. Conclusions: One in six ELGA survivors at age 16 years have severe disabilities and are in special schools. Most ELGA survivors are in mainstream school and are coping well as they enter adult life, although some will continue to need additional health, educational, and social services.